Reactive magnetron cosputtering of hard and conductive ternary nitride thin films: Ti–Zr–N and Ti–Ta–N - Abadias, Gregory; Dub, Sergey N.; Koutsokeras, Loukas E. (My University, 2010)
Ternary transition metal nitride thin films, with thickness up to 300 nm, were deposited by dc reactive magnetron cosputtering in Ar- N2 plasma discharges at 300 °C on Si substrates. Two systems were comparatively studied, Ti-Zr-N and Ti-Ta-N, as representative of isostructural and nonisostructural prototypes, with the aim of characterizing their structural, mechanical, and electrical properties. While phase-separated TiN-ZrN and TiN-TaN are the bulk equilibrium states, Ti1-x Zrx N and Ti 1-y Tay N solid solutions with the Na-Cl (B1 -type) structure could be stabilized in a large compositional range (up to x=1 and y=0.75, respectively). Substituting Ti atoms by either Zr or Ta atoms led to significant changes in film texture, microstructure, grain size, and surface morphology, as evidenced by x-ray diffraction, x-ray reflectivity, and scanning electron and atomic force microscopies. The ternary Ti1-y Ta y N films exhibited superior mechanical properties to Ti 1-x Zrx N films as well as binary compounds, with hardness as high as 42 GPa for y=0.69. All films were metallic, the lowest electrical resistivity ρ ∼65 μΩ cm being obtained for pure ZrN, while for Ti1-y Tay N films a minimum was observed at y∼0.3. The evolution of the different film properties is discussed based on microstructrural investigations
Keywords: Titanium nitride; Magnetron sputtering; Ion plating